Discovery and expression of insecticidal proteins via genome mining of novel Bacillus thuringiensis strain Bt1Fo - Kobilov, Fazliddin B.; Li, Pengwei; Nazirov, Muhammad-Latif M.; Chen, Meng; Miralimova, Shakhlo; Yakubov, Iskandar; Asrorov, Akmal M.; Sohibnazarova, Khonsuluv; Azimova, Nodira; Khalilov, Ilkhom; Yusupov, Ulugbek; Chen, Yihua; et al. (Frontiers in Microbiology, 2025)
The identification of environmentally friendly pesticides and insecticidal agents is crucial for developing sustainable agricultural practices. Bacillus thuringiensis exemplifies such a microbial agent, effectively controlling pests across a wide range of agronomic crops. In this study, we characterized the native strain Bt1Fo, which exhibits potent activity against major crop pests in the Lepidoptera order. All six types and truncated forms of the Cry1Aa and Cry1Ac insecticide proteins were expressed in E. coli, and recombinant proteins demonstrated strong activity against Helicoverpa armigera, with full-length Cry1Aa/1Ac and Vip3Aa being the most potent. Importantly, Cry1Ia exhibited high toxicity against H. armigera, representing its first documented efficacy against this major pest. These findings support Bt1Fo as a genetically stable source of multi-toxin biopesticides and provide a new opportunity for resistance management and further elucidation of the molecular interactions between insect midgut receptors and downstream signaling components.